2021
DOI: 10.1186/s13071-021-04607-7
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal patterns and spatial variation of Borrelia burgdorferi (sensu lato) infections in Ixodes ricinus in the Netherlands

Abstract: Background The incidence of Lyme borreliosis varies over time and space through as yet incompletely understood mechanisms. In Europe, Lyme borreliosis is caused by infection with a Borrelia burgdorferi (s.l.) genospecies, which is primarily transmitted by a bite of Ixodes ricinus nymphs. The aim of this study was to investigate the spatial and temporal variation in nymphal infection prevalence of B. burgdorferi (s.l.) (NIP), density of questing nymphs (DON) and the resulting density of infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…Ixodes spp. tick bites can occur throughout the year but have a higher prevalence in summer when tick populations, especially biting nymphs, are at their peak, which is also associated with the highest occurrence of Lyme disease (23). We observed that I. ricinus ticks were frequently infected by Borrelia sp.…”
Section: Discussionmentioning
confidence: 71%
“…Ixodes spp. tick bites can occur throughout the year but have a higher prevalence in summer when tick populations, especially biting nymphs, are at their peak, which is also associated with the highest occurrence of Lyme disease (23). We observed that I. ricinus ticks were frequently infected by Borrelia sp.…”
Section: Discussionmentioning
confidence: 71%
“…Infection with B. burgdorferi in dogs and cats leads to seroconversion, but direct relation with the disease development is still contentious (Littman et al 2018). Humans are mostly bitten by I. ricinus nymphs (Hartemink et al 2021), therefore the infection of B. burgdorferi s.l. in nymphs (4.1%) is of medical importance.…”
Section: Discussionmentioning
confidence: 99%
“…Wild Peromyscus leucopus mice are the main murine reservoir in north-east America and Apodemus flavicollis mice in Europe. 6,[97][98][99] To interrupt the vector-reservoir-host life cycle of Borrelia spirochaetes, several research groups have focused on reservoir-targeted vaccination of the murine reservoir. Reservoir-targeted vaccines are especially attractive for the control of tick-borne diseases as multi-host life cycle ticks will interact with wild life as well as pets, livestock and humans, and pathogens can be passed through tick generations using a wild life reservoir.…”
Section: Re S Ervoir-targ E Ted Vaccine Smentioning
confidence: 99%